The Principle of Subsidiarity and the Multilevel Citizenship: The Future of Social Inclusion - Raimondo Cagiano de Azevedo; Angela Paparusso; Mauro Vaccaro (Culture e Studi del Sociale)
The principle of subsidiarity was formally introduced in the European Union’s legislation framework in 1992 with the Treaty of Maastricht; although already in 1986, the European Single Act authorized Community action only if a specific objective could be better attained at the Community level. However, the subsidiarity principle inspiring the functionalist approach – according to which the best solution is always the most effective – can be found already in the Vedel Report (25 March 1972), aimed at examining the problem of the extension of the powers of the European Parliament. The principle of subsidiary is the reorganization of authority in the European Union (EU), an important policy-creating process in which authority and policy-making influences are shared across multiple levels of government.